(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The traditional teaching methods have been utilizing for years. The strategies need to be improved to be able to adapt with current knowledge and also the students. Flipped classroom is fairly new in the teaching field as a strategy for teaching. As with most strategies, the flipped classroom has a variety of ways to implement not only for students but also the instructors. In this paper, we introduce and analyze the methods being used as new teaching methods in schools. We review and provide research on the implementation of the flipped classroom. We also provide some results of applying the flipped classroom methods and explain them to clarify advantages and disadvantages of the strategies.